PEDAGOGICAL POSSIBILITIES OF DEVELOPING EARLY CHILDHOOD SPEECH (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The article discusses the pedagogical possibilities of developing early childhood speech from a scientific and theoretical perspective. The study analyzes the psychological and pedagogical features of early childhood speech development, the main factors influencing speech formation, and the importance of the educational environment. It also examines the interrelationship of play activities, communication, the exemplary role of adult speech, and sensory development processes in the development of children's speech.